Auditoría operativa al área de fumigación de la compañía Aerofaq en el cantón Valencia periodo 2012 - Herrera Pucha, Ruth Melania (2015)
This research is directed to the implementation of an operational audit the area of fumigation, the company AEROFAQ CIA. LTDA, during the period 2012.; This study aims to perform from the operational perspective and compliance with the goals, objectives and policies that have the organization, this project also responds to the main research question, whith was documentary that its objective was achieved with the implementation of the operational audit on existing general nature and whose effects are known in the professional field of Accounting. Practice is considered that the information necessary to achieve the stated objective was obtained directly from reality. Methods such as inductive, deductive and analytical were used, are considered to be the most appropriate when executing an audit is about. As for the techniques, it became necessary to resort to the interview because it is the most direct method to obtain information from the caller; the development of this study in the same measure to evaluate the internal control by a pre-determined to learn more about the control system of the company questionnaire; the evaluation system of internal control in the spraying area of the company, it was determined that the process established in the planning continues, however they are prone to certain changes of continuous improvement. It was determined that in the area of fumigation processes and operational activities need more of development of each worker. The audit report of the fumigation area was conducted.